2018
DOI: 10.1016/j.redox.2018.05.009
|View full text |Cite
|
Sign up to set email alerts
|

A silver lining for 24-hydroxycholesterol in Alzheimer's disease: The involvement of the neuroprotective enzyme sirtuin 1

Abstract: It is now established that cholesterol oxidation products (oxysterols) are involved in several events underlying Alzheimer's disease (AD) pathogenesis. Of note, certain oxysterols cause neuron dysfunction and degeneration but, recently, some of them have been shown also to have neuroprotective effects. The present study, which aimed to understand the potential effects of 24-hydroxycholesterol (24-OH) against the intraneuronal accumulation of hyperphosphorylated tau protein, stressed these latter effects. A ben… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 48 publications
2
32
0
Order By: Relevance
“…For example, 24-hydroxycholesterol (24-OHC) can impede hyperphosphorylation of tau induced by deposition of Aβ in SK-N-BE cells by regulating the deacetylase sirtuin 1. As a neuroprotective oxysterol, 24-OHC was also validated to modulate synaptic function in hippocampal neurons of rats through LXR (Testa et al, 2018). Furthermore, genomewide association studies (GWAS) verified that some genes like ABCA7, TREM2, DAPK1, and ADAMTS1 were associated with AD.…”
Section: Discussionmentioning
confidence: 96%
“…For example, 24-hydroxycholesterol (24-OHC) can impede hyperphosphorylation of tau induced by deposition of Aβ in SK-N-BE cells by regulating the deacetylase sirtuin 1. As a neuroprotective oxysterol, 24-OHC was also validated to modulate synaptic function in hippocampal neurons of rats through LXR (Testa et al, 2018). Furthermore, genomewide association studies (GWAS) verified that some genes like ABCA7, TREM2, DAPK1, and ADAMTS1 were associated with AD.…”
Section: Discussionmentioning
confidence: 96%
“…In these cells, 7KC-induced cell death was attenuated by 24S-OHC [109]. Human SK-N-BE neuroblastoma cells were also treated with 7KC at the physiopathological concentration of 1 µM with the aim of comparing the effects of 7KC and 24S-OHC on tau phosphorylation, and to study the abilities to modulate the SIRT1-dependent neuroprotective pathway [110]. SK-N-BE cells were also used to compare the cytotoxicity of 7KC and 7β-OHC.…”
Section: -In Vitro Models Applied To the Study Of Neurodegenerative Diseases And The Identification Of Cytoprotective Compounds In This Fmentioning
confidence: 99%
“…As regards 24-OHC, contrasting effects have been reported: on the one hand it promotes neuroinflammation, Aβ peptide production, oxidative stress, and cell death in neuronal cell lines (Gamba et al, 2011, 2014; Yamanaka et al, 2011; Testa et al, 2014); on the other hand, it has been reported to play an important role in regulating brain cholesterol metabolism via LXR, and to exert beneficial effects such as preventing tau hyperphosphorylation in SK-N-BE cells, suppressing Aβ production in SH-SY5Y cells, and regulating synaptic function in rat hippocampal neurons and slices (Paul et al, 2013; Urano et al, 2013; Testa et al, 2018b). These opposite effects may depend on 24-OHC concentration, since low concentrations (1–10 μM) seem to induce adaptive responses and beneficial effects in neuronal cell lines as discussed by Testa et al (2018a).…”
Section: The Complex Role Of Cholesterol In the Brainmentioning
confidence: 99%